Tension–compression asymmetry of 〈c+a〉 slip in Ti–6Al. (15th March 2020) - Roberts, William; Gong, Jicheng; Wilkinson, Angus J.; Tarleton, Edmund
Graphical abstract: Abstract: Microcantilevers with triangular cross-sections were machined using a focused ion beam from an α Ti–6Al alloy. Plasticity was predominantly in the lower part of the cantilever, allowing tension–compression asymmetry to be investigated by bending the cantilever up or down. Both ⟨ a ⟩ prismatic slip and 〈 c + a 〉 pyramidal slip were investigated. The critical resolved shear stress was determined by calibrating a crystal plasticity model and found to be 329 MPa for ⟨ a ⟩ prismatic slip in both tension and compression. However significant tension–compression asymmetry was observed for 〈 c + a 〉 pyramidal slip; increasing to 820 MPa under compression and decreasing to 558 MPa in tension.